Quando Sísifo alcança o topo da montanha: escolarização de longo curso, vida socioprofissional e disposições culturais de sujeitos de origem popular - Luiz Fernando de Oliveira (2017)
The present thesis results from a research inserted in the field of Sociology of Education, specifically amongst the studies based on qualitative data and developed in the microsociological scale. It also comprehends certain concepts of General Sociology. The main goal of the research was to understand how four long-schooled subjects from the low class walk of life, who work in professions that are in keeping with the higher education capital they have acquired and which have gone through social ascension processes are related to diverse cultures present in different material and symbolic universes, namely: the culture of their respective means of both social and family origins, also professional and legitimate culture, the one most commonly related to the cultural dispositions of the economically superior social class. The studied subjects age ranges from 53 to 68 years old, being them: Edmar (formerly a Brazilian Merchant Marine Officer, Civil Engineer, although he does not work in this profession, and a basic education teacher), Sebastião (a retired university professor and a basic education teacher), Vicente (a retired university professor) and Gilberto (Judge of Law). The fieldwork was basically consisted of in-depth interviews with the four subjects regarding the constructed object. The data collection began in March 2013 (through informal interviews, with previously duly authorized recordings by the interviewees at the time of the work formalization and academic and ethically validated by the prediction of their use in the submitted projects to university bodies responsible for the ethical and scientific evaluation of this research) and was finished in July 2017, when a last complementary interview was conducted with one of the subjects. The results of the research point to certain hypotheses that seem to find validity in the individual scale, especially in the four analyzed cases. Such hypotheses can be summarized as follows: through higher education, but mainly through informal processes of socialization in the world of labor, the subjects seem to have incorporated the specific culture of their respective areas of professional activity with an intensity that was able to grant them a longer continuance in their occupations and to guarantee them a stable and progressive professional development; the subjects relationship approach with the legitimate culture is varied, as it is diverse the degrees of their incorporation, however, the greater or less familiarity with this culture seems not to interfere directly in the processes that involve, in general, those interviewed professional and social lives; finally, there seems to be a social and cultural non-desertion effort from those interviewed, expressed in a real struggle waged by them against the possibility of distancing themselves from their origins.